Increased production of hydrogen peroxide by peripheral blood monocytes associated with smoking exposure intensity in smokers - Tanni Suzana E; Correa Camila R; Angeleli Aparecida Y; Vale Simone A; Coelho Liana S; Godoy Irma (BMC, 2012)
Abstract Background Smoking is known to be associated with oxidative stress; however, it has not been elucidated whether the oxidative response is influenced by the intensity of smoking exposure. Objectives Evaluate the effect of smoking exposure on the secretion of hydrogen peroxide (H2O2) by the peripheral blood monocytes of smokers. Methods A total of 25 smokers (50.3±8.8 years, 48% male) underwent the following evaluations: spirometry, pulse oximetry, body composition and total peripheral blood count. Peripheral blood monocyte (PBM) cultures were isolated and maintained, and IL-6 and TNF-α were measured in the plasma and in the supernatants of spontaneous and stimulated cultures. H2O2 was evaluated in the supernatants of the PBM cultures, and a subset of the PBM culture supernatants was stimulated with phorbol myristate acetate (PMA). We also evaluated 38 healthy controls (49.1±8.2 years, 42% male). Results The spontaneous and stimulated monocytes' secretion of H2O2 were statistically higher in the smokers than in the healthy controls (p<0.001). The H2O2 secretions were statistically significant higher after stimulation with PMA in both groups (p<0.001). In the multiple regression analysis, we identified a positive, statistically significant association between pack-years of smoking and the spontaneous secretion of H2O2 by PBM culture, adjusted for potential confounding variables. The association between PBM culture secretion of H2O2 and the production of TNF-α and IL-6 was not significant. Conclusion We identified a positive association between higher production of H2O2 in smokers and higher smoking exposure during life. The influence of pack-years smoking may be a key modifiable factor in oxidative stress associated to smoking.